Effects of Caloric Intake on Learning and Memory Function in Juvenile C57BL/6J Mice. (27th September 2015) - Xu, Bao-Lei; Wang, Rong; Ma, Li-Na; Dong, Wen; Zhao, Zhi-Wei; Zhang, Jing-Shuang; Wang, Yu-Lan; Zhang, Xu
Abstract : Dietary composition may influence neuronal function as well as processes underlying synaptic plasticity. In this study, we aimed to determine the effect of high and low caloric diets on a mouse model of learning and memory and to explore mechanisms underlying this process. Mice were divided into three different dietary groups: normal control ( n = 12 ), high-caloric (HC) diet ( n = 12 ), and low-caloric (LC) diet ( n = 12 ) . After 6 months, mice were evaluated on the Morris water maze to assess spatial memory ability. We found that HC diet impaired learning and memory function relative to both control and LC diet. The levels of SIRT1 as well as its downstream effectors p53, p16, and peroxisome proliferator-activated receptor γ (PPAR γ ) were decreased in brain tissues obtained from HC mice. LC upregulated SIRT1 but downregulated p53, p16, and PPAR γ . The expressions of PI3K and Akt were not altered after HC or LC diet treatment, but both LC and HC elevated the levels of phosphorylated-cAMP response element-binding protein (p-CREB) and IGF-1 in hippocampal CA1 region. Therefore, HC diet-induced dysfunction in learning and memory may be prevented by caloric restriction via regulation of the SIRT1-p53 or IGF-1 signaling pathways and phosphorylation of CREB.